TI_GERICHTE 15.2018.77 vom 26. März 2019 , Sequestro di un conto bancario. Rivendicazione. Perenzione del diritto di rivendicare - TI Tribunale d'appello (2019)
Sequestro di un conto bancario. Rivendicazione. Perenzione del diritto di rivendicare